Damian Zdrada, „Seksoholizm, perwersja i miłość”, Wydawnictwo Difin SA, Warszawa 2017, s. 264. - Wiesław , Kraiński (Studia Gdańskie, 2018)
Damian Zdrada, „Seksoholizm, perwersja i miłość”, Wydawnictwo Difin SA, Warszawa 2017, s. 264.